Towards a model public sector integrity commission - Prenzler, Tim; Faulkner, Nicholas (2010)
This article examines the current debate in Australia about public sector integrity and the idea of a standing anticorruption commission. From this debate the article outlines a specific type of 'public sector integrity commission' that in principle should have the necessary powers and techniques at its disposal to minimise corruption while ensuring efficiency and fairness. The debate has been most active in jurisdictions that have not had an anticorruption commissions - mainly in Victoria, South Australia and Tasmania - but debate about integrity commissions has occurred in all jurisdictions. The authors argue that anticorruption commissions are essential to ensure the integrity of the public sector and that a model commission should: cover all elements of the public sector; independently investigate serious and mid-level complaints; have own motion powers to investigate any matter; have summary authority to apply administrative sanctions; make use of a range of investigative tools; not be tasked with combating major and organised crime; and be held accountable to citizens through a parliamentary committee and a parliamentary inspector. - Reproduced.
Keywords: Corruption